Insulin-like growth factors and IGF binding proteins in cyst fluid from patients with craniopharyngioma prior to intracavitary irradiation with 90Yttrium and thereafter. Issue 1 (February 1996) - Zumkeller, W; Sääf, M; Rähn, T
Abstract : Aim —To examine a series of cyst fluid samples from patients with craniopharyngioma at various stages of treatment in order to evaluate the use of insulin-like growth factors (IGFs) and IGF binding proteins as tumour markers or indicators of successful treatment, or both. Methods —Cyst fluid samples were obtained by stereotactic puncture prior to the intracavitary application of 90 Yttrium and at subsequent occasions. Analysis was performed by gel chromatography, radio-immunoassays, binding studies, and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) with subsequent western blotting. Results —IGF-I, -II and IGF binding protein-1 concentrations were measured in three craniopharyngioma cyst fluid samples. Immunoreactive IGF-I and IGF binding protein-1 concentrations in these three samples were between 6 and 29 ng/ml, and 17 and 48 ng/ml, respectively. In contrast, the IGF-II concentrations measured in 19 cyst fluid samples from seven patients with craniopharyngioma at various stages of treatment were much higher at 25-671 ng/ml. SDS-PAGE and subsequent western blotting using [ 125 I]IGF-II as the ligand gave bands with estimated molecular weights of 330, 220, 135, 96, 46, 43, 34, 29, and 13·5 kDa in one adult, and identical bands at 220, 41·5, 37·5, 32, and 19 kDa in three cyst fluid samples from three children with craniopharyngioma. Conclusions —These results suggest that IGFs and IGF binding proteins are secreted by craniopharyngiomas and that they may alter the growth characteristics of these tumours. Furthermore, the distinct pattern of IGF binding protein sizes might be used as a tool for the differential diagnosis of tumours of the central nervous system.